Windows into the Thinking of an Experienced Teacher Exploring the Influence of Spontaneous "Talk Aloud" in Practice - Loughran, John. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1995)
Reflection is a commonly used term in teacher education. Its meaning and use, however, varies from person to person and from program to program. Despite these variations, there is agreement that the goal of preparing reflective practitioners is a worthwhile endeavor in teacher education. The purpose of reflecting is to untangle a problem, or to make sense of a puzzling situation; reflection involves working toward a better understanding of the problem and ways of solving it. The first half of this paper is an extensive literature review on reflection in teacher education. The second half of the paper explores a conceptual framework constructed in the belief that if reflection on action is to be understood and valued by student-teachers, then it cannot be presented as an isolated event or process, but must be an integral component in the curriculum. The framework is illustrated by a case study designed to explore the relationship between the modeling of reflective practice and its development in and use by student teachers, and to demonstrate the effect this modeling has on one student teacher. The study indicates that three distinct periods of thinking occur--before, during, and after the lesson. During these periods there are opportunities for anticipatory, contemporaneous, and retrospective reflection. (Contains 25 references.) (ND)
ERIC Note: Paper presented at the Annual Meeting of the American Educational Research Association (San Francisco, CA, April 18-22, 1995).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Case Studies; Cognitive Style; Elementary Secondary Education; Foreign Countries; Higher Education; Literature Reviews; Models; Preservice Teacher Education; Reflective Teaching; Student Teachers; Teacher Education Programs; Teaching Experience; Reflection Process -- Reflective Practice; Australia -- Reflective Thinking; Information Analyses; Reports, Research; Speeches/Meeting Papers